Survey on Antibiotic Practices in Chittagong City of Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
We aimed to determine the amount of antibiotic prescribed by physicians and also sold by pharmacies in Chittagong city of Bangladesh by using a cross sectional survey. Patients, physicians, pharmacies and prescriptions based study was conducted in May 01, 2012 to May 30, 2012. A total of 118 prescriptions were collected and 82 local pharmacies were selected for data collection about daily sales of antibiotics. It was evident that 69.49% of the prescriptions contained antibiotics. Azithromycin and cefixim were found to be the most preferred antibiotics in physicians prescriptions survey. On the other hand, it was evident from the pharmacy survey (without prescription) selling rates of azithromycin and ciprofloxacin were more predominant. The diseases which were seen in the studies include cough, typhoid, diarrhea, nausea, chronic UTI, RTI, fever and rhinitis. The result of the present survey indicates that antibiotics are widely and inappropriately practiced without following standard guidelines. This is an alarming condition in the health sector of Bangladesh and therefore, the respective authority should take necessary steps to minimize the harmful effects of antibiotics.Bangladesh Pharmaceutical Journal 18(2): 174-178, 2015